Decrypting China's self-image as "great power" - Nele Noesselt; Tanja Eckstein; Elizaveta Priupolina (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2021)
This paper explores the visual representation of the Chinese concept of daguo (literally: great power / major power) based on the 2017 CCTV documentary Daguo Waijiao 大国外交 (Major Power Diplomacy). Drawing on a combination of select streams of National Role Theory (NRT) and Social Identity Theory (SIT), the paper assesses the Chinese role claims and visualized role performance vis-à-vis two significant others, the Soviet Union / Russia and the US. The coding of select cases of the PRC's daguo role enactment sheds light on the conceptual, socio-psychological underpinnings of China's self-identity and global status reflections in the 21st century and hence offers some rare insight into the black box of the hermetically closed Chinese party-state.
Keywords: 330; China; daguo; national role theory; Russia; social identity theory; visualized narratives; US